Analysis of Current User Stickiness Marketing Strategies and Future Enhancement Means of Online Game Companies: A Case Study Based on miHoYo - Zhou, Jinqiang (Transactions on Economics, Business and Management Research, 2024)
With the growing influence of miHoYo’s game products such as Original God at home and abroad, more and more people know miHoYo through the company’s high-quality handheld games. miHoYo holds more than half of the market share in China and has a large number of loyal players. However, as the game content is updated, there is no lack of old players giving up and quitting, how to retain these players for a long time and attract new players to play their own games has become the most important question for all game companies, and miHoYo has given the perfect answer. miHoYo has set up its own social platform software online, set up incentive programmes for creators on its creative platforms and so on, and has also participated in comic shows, advertisements, as well as in the "Manga" and "Battle of the Bulletin Boards".Events such as Comic-Con, advertising campaigns, and linkages with merchandise and tourist attractions create a wonderful and enjoyable gaming community and environment for players, who offline feel the atmosphere of having fun on-site, as well as gaining a sense of empathy between the game and themselves. The combination of the two makes miHoYo’s games highly discussed and trafficked both on online platforms and in real life. This makes miHoYo’s players more interested in miHoYo’s game products, as well as having a strong sense of trust in miHoYo, which finally makes miHoYo’s gamers much stickier than other game companies in the market.